糞特有ステロイドの分析による屎尿汚染の鑑別例と人畜汚染指標に与える配合飼料中のステロイドの影響について - 本多, 正夫; 篠原, 利明 (衛生化学, 1987)
This Article reports on the discrimination of animal species by analysis of fecal steroids with respect to the illegal disposal of fecal polluted matters. The pollution indicator, the compositional ratio of 24-ethylcoprostanol to coprostanol on gas chromatographic profile was satisfactorily put in practical application. Twenty one subjects were examined for the discrimination, given as mostly polluted water by pig, cattle, and human excretions. The indicator values of these samples were ranged from 0.12 to 0.28 for human (9 samples), from 0.50 to 0.62 for pig (7 samples). One example of beef cattle gave a value of 1.30,and two subjects of cow excretion showed the values of 1.0 and 1.1. These results were all in good agreement with the criteria of human (x^^-, 0.17 ; σx, 0.06 ; γ, 0.77), pig (x^^-, 0.57 ; σx, 0.18 ; γ, 0.70), cow (x^^-, 1.33 ; σx, 0.20 ; γ, 0.94), and beef cattle (Holstein, x^^-, 1.65 ; σx, 0.40 ; γ, 0.65), respectively. Effects of sterol composition in the assorted feeds for pig or cattle on the fecal pollution indicators were investigated. The results showed that main components affecting the indicator value were cholesterol, coprostanol reduced from cholesterol by intestine microorganisms, β-sitosterol, predominantly distributed in plant seeds, and 24-ethylcoprostanol, metabolite from β-sitosterol.